Efficient and Effective Computer-based Library Management System - Jumaa, Bassim Abdulbaki; Saleem, Maysoon Allawi (lark, 2019)
EECLMS is Efficient and Effective Computer–based Library database Management System that was developed for and Implement at dentistry collage to meet user unique requirements and preoperational of functional Specification for library manumit with new and special fleetest which cannot be found in other systems. The present of status of requirements is outlined as the basis for describing the problem (Traditional Library Management System) which EECLMS is intended to deal with and solve a database has been design to fit the above requirements using Microsoft/access. Visual basic programming language has been chosen to be the tool for developing the algorithms to make full control of the database designed. The result was a complete library management system with state of the art in basic programming and user–friendly system with many unique and new features which can be represented by (1) flexibility, (2) reliability, (3) multi–language; (4) high security issues (5) attraction graphical user interfaces and other features.